2022
DOI: 10.1177/18333583221107713
|View full text |Cite
|
Sign up to set email alerts
|

Performance of hospital administrative data for detection of sepsis in Australia: The sepsis coding and documentation (SECOND) study

Abstract: This content has been temporarily removed for correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
(60 reference statements)
2
5
0
Order By: Relevance
“…Notably, while 35% of patients admitted direct to the ICU from ED were identified by trained research coordinators as meeting the pre‐defined survey inclusion criteria for sepsis, in less than one‐third of those patients the ICU admission APACHE III diagnostic code extracted from the patient's medical record was sepsis or sepsis with shock. This apparent underestimation of community‐onset sepsis case detection in hospital administrative databases, as compared with clinical review of medical records, is consistent with previous reports 26 …”
Section: Discussionsupporting
confidence: 91%
“…Notably, while 35% of patients admitted direct to the ICU from ED were identified by trained research coordinators as meeting the pre‐defined survey inclusion criteria for sepsis, in less than one‐third of those patients the ICU admission APACHE III diagnostic code extracted from the patient's medical record was sepsis or sepsis with shock. This apparent underestimation of community‐onset sepsis case detection in hospital administrative databases, as compared with clinical review of medical records, is consistent with previous reports 26 …”
Section: Discussionsupporting
confidence: 91%
“…Kilkenny et al (2022) reported variation in the reporting of comorbidities of stroke in administrative data suggesting the need to improve clinical documentation. Duke et al (2022) examined coding-based definitions for sepsis and identified significant differences in sepsis classification in administrative data (e.g. use of explicit ICD10-AM diagnosis codes was poorly predictive of sepsis, with low sensitivity).…”
Section: Virtual Special Issue On CDImentioning
confidence: 99%
“…The significance of clinical coding as impacted by CDI has been alluded to in a number of articles in the VSI collection that describe issues experienced by specific clinical programmes where information was not available in a form that supported the programme. Strategies to address the limitations of administrative coded data and lack of specificity in support of CDI have been proposed by Duke et al (2022), Payton et al (2023) and Sierla and Dylke (2023). In their editorial on the emergence of health information in aged care, Loggie and Davis (2023) discussed needed improvements in clinical documentation related specifically to the aged care sector.…”
Section: Virtual Special Issue On CDImentioning
confidence: 99%
See 2 more Smart Citations